(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
Three samples of alumina_zirconia mixed oxid AL2O3_Zr2O4(1;0.25;0.1) mole ratio based on oxides were prepared by sol-gel precipition method. The system AL2O3_Zr2O4 was obtained by mixing tow gel of alumina and zirconia precipited from aqueous solutions of alumina nitrate and zirconium chlorid using ammonium hydroxide solution as precipited agent. The system after mixing was allwed to settle for 24 h. The resuling precipitate was filtered off and washed several times with deionized water and dried at 120°C for 24 h. The powdered oven-dried hydrous alumina_zirconia was immersed in ammonium sulfate solution(1) M for 24 h to incorporate sulfate ions. The resulting sample was dried at 120° C for 24 h, calcined at 550°C for 6 h. The textural properties were determined by terating of adsorption data of N2 at 77 K, and the results showed the changings in the textural properties.The TG_DTA analysis showed the thermal stable of the samples in a long rang of temperature. FTIR spectra showed that the sulfate ions were incorperated in the saples.